2018
DOI: 10.1111/radm.12320
|View full text |Cite
|
Sign up to set email alerts
|

Partial adjustment toward target R&D intensity

Abstract: Existing research assumes that once firms have determined their target R&D intensity, they can adjust instantaneously and fully to their target R&D intensity, regardless of their past R&D intensity. In this study, we draw on the partial adjustment framework to examine the dynamics of firms' adjustment toward their target R&D intensity. We find that firms usually do not adjust instantaneously or fully to their target R&D intensity; they typically close half of the gap between their past and target R&D intensity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 65 publications
0
7
0
2
Order By: Relevance
“…We have shown earlier that a highly positive net charge and the presence of a fatty acid are important in complex formation between Transportan analogs and siRNA. 19 Several groups have used a stearic acid modification in histidine containing peptides, 16,25,26 but it has been shown that the length of the fatty acid chain plays a role in the transfection efficacy of nucleic acids by CPPs. 27 Therefore, in order to optimize the hydrophobicity with the fatty acid tail, and to test the optimal conditions for each peptide sequence, saturated fatty acid modifications of C18, C20 or C22 were tested.…”
Section: Design Of Ph-sensitive Histidine Containing Nickfect Peptidesmentioning
confidence: 99%
“…We have shown earlier that a highly positive net charge and the presence of a fatty acid are important in complex formation between Transportan analogs and siRNA. 19 Several groups have used a stearic acid modification in histidine containing peptides, 16,25,26 but it has been shown that the length of the fatty acid chain plays a role in the transfection efficacy of nucleic acids by CPPs. 27 Therefore, in order to optimize the hydrophobicity with the fatty acid tail, and to test the optimal conditions for each peptide sequence, saturated fatty acid modifications of C18, C20 or C22 were tested.…”
Section: Design Of Ph-sensitive Histidine Containing Nickfect Peptidesmentioning
confidence: 99%
“…The lengths of gas bubbles and liquid slugs are mainly affected by the different bubble-forming mechanisms as discussed in detail by Ganapathy et al [86] and Fu et al [87]. Research agrees that the inlet design also significantly influences the generated lengths [87][88][89][90][91]. Scaling laws for often employed T-and Y-junctions and rarely applied other inlets such as showerheads and membranes may be found, e.g., in [92][93][94][95].…”
Section: Gas Bubble and Liquid Slug Lengthsmentioning
confidence: 89%
“…They also find that these target leverage ratios typically vary a lot in different years and across different firms. Given that the partial adjustment model is a useful framework to analyse the dynamics of an interested variable with target setting, it has also been extended beyond the capital structure adjustment and applied in economic literature including governance structure (Wintoki et al 2012), risk taking (Calvet et al 2009) and R&D intensity (Chen 2018). Our work aims to shed light on studying the dynamics of the CO 2 intensity movement across time, and its relationship with the financial development factor by applying this useful tool in the climate change literature.…”
Section: Literature Reviewmentioning
confidence: 99%